Development of UASB–DHS system for anaerobically-treated tofu processing wastewater treatment under ambient temperature. Issue 25 (10th November 2022) - Asano, Kenya; Watari, Takahiro; Hatamoto, Masashi; Yamaguchi, Takashi
ABSTRACT: Tofu is widely processed in East and Southeast Asian countries. During the production, highly polluted wastewater is discharged. This wastewater is commonly treated using a high-rate anaerobic wastewater treatment process; however, several organic compounds and nitrogen remain in the anaerobic effluent. The aim of this study was to develop a combined upflow anaerobic sludge blanket (UASB) and downflow hanging sponge (DHS) biosystem that that serves as a post-treatment for an expanded granular sludge blanket reactor used for treating tofu-processing wastewater in Japan for 699 days. The UASB reactor played a role in treating of COD, with 58 ± 16% and 74 ± 20% of total COD and soluble COD removed anaerobically. Besides, methane was recovered from removed soluble COD were 63 ± 28% and 87 ± 64% at winter and summer. Meanwhile, the DHS reactor showed its potential in treatment of BOD and TSS. The final effluents were recorded as 67 ± 38 mg L −1, 50 ± 26 mg L −1, and 22 ± 16 mg L −1 of total COD, BOD and total suspended solids, respectively. This indicates that the proposed UASB-DHS system has proven its suitability as post-treatment system for anaerobically treated tofu-processing wastewater. GRAPHICAL ABSTRACT: UF0001